A framework for the science contribution in climate adaptation: Experiences from science-policy processes in the Andes. Issue 47 (March 2015) - Huggel, Christian; Scheel, Marlene; Albrecht, Franziska; Andres, Norina; Calanca, Pierluigi; Jurt, Christine; Khabarov, Nikolay; Mira-Salama, Daniel; Rohrer, Mario; Salzmann, Nadine; Silva, Yamina; Silvestre, Elizabeth; et al.
Highlights: Although a policy priority, climate adaptation needs more methodological guidance. A framework is proposed for the science contribution in the climate adaptation process. An interdisciplinary scientific scope is thereby essential. The importance of joint problem framing and knowledge production is underlined. Scarce socio-environmental data may represent a barrier to successful adaptation. Abstract: As significant impacts of climate change are increasingly considered unavoidable, adaptation has become a policy priority. It is generally agreed that science is important for the adaptation process but specific guidance on how and to what degree science should contribute and be embedded in this process is still limited which is at odds with the high demand for science contributions to climate adaptation by international organizations, national governments and others. Here we present and analyze experiences from the tropical Andes based on a recent science-policy process on the national and supra-national government level. During this process a framework for the science contribution in climate adaptation has been developed; it consists of three stages, including (1) the framing and problem definition, (2) the scientific assessment of climate, impacts, vulnerabilities and risks, and (3) the evaluation of adaptation options and their implementation. A large amount of methods has been analyzed for stage (2), and a number of major climate adaptation projects in the region assessed for (3). Our study underlines the importance of joint problem framing among various scientific and non-scientific actors, definition of socio-environmental systems, time frames, and a more intense interaction of social and physical climate and impact sciences. Scientifically, the scarcity of environmental, social and economic data in regions like the Andes continue to represent a limitation to adaptation, and further investments into coordinated socio-environmental monitoring, data availability and sharing are essential.